Estimation of tissue osteopontin levels before and after different traditional therapeutic modalities in psoriatic patients. (2nd January 2012) - El‐Eishi, N.H.; Kadry, D.; Hegazy, R.A.; Rashed, L.
Abstract Background Several lines of evidences support a major role for Th1 cells in psoriasis. Treatment of psoriasis with cyclosporine, methotrexate and psoralen plus ultraviolet A (PUVA) is associated with clinical improvement and decrease in epidermal hyperplasia. Osteopontin (OPN) exerts a T‐helper type 1 (Th1) cytokine function, regulating inflammatory cell accumulation and function. Objective To detect the effects of methotrexate, cyclosporine and PUVA on OPN expression in psoriatic plaques, and whether these changes correlate with clinical response. Methods For three groups of psoriatic patients (each including 12 patients), the Psoriasis Area Severity Index (PASI) and levels of lesional skin OPN were determined using enzyme‐linked immunosorbent assays before and after treatment with methotrexate, cyclosporine or PUVA. Skin biopsies from 20 healthy volunteers served as control for OPN levels in normal skin. Results Baseline lesional skin of psoriatic patients showed a statistically significant elevation of OPN levels in comparison to controls. Three months after therapy, the three therapeutic modalities were associated with a significant decrease in the mean levels of PASI and tissue OPN, with the PUVA group showing the highest level of reduction in OPN levels and cyclosporine group showing the highest level of reduction in PASI. Conclusion Our study points to the possible role played by OPN in the pathogenesis of psoriasis and in reflecting disease severity. These standard therapeutic modalities used in the current study were associated with a significant decrease in PASI and OPN levels. They constitute highly effective therapeutic modalities for psoriasis, which might exert their anti‐psoriatic activity partially through altering the expression of OPN.